Genome-wide analysis of UDP-glycosyltransferase gene family and identification of members involved in flavonoid glucosylation in Chinese bayberry (Morella rubra) - Ren, Chuanhong; Cao, Yunlin; Xing, Mengyun; Guo, Yan; Li, Jiajia; Xue, Lei; Sun, Chongde; Xu, Changjie; Chen, Kunsong; Li, Xian (Frontiers in Plant Science, 2022)
Glycosylation was catalyzed by UDP-glycosyltransferase (UGT) and was important for enriching diversity of flavonoids. Chinese bayberry (Morella rubra) has significant nutritional and medical values because of diverse natural flavonoid glycosides. However, information of UGT gene family was quite limited in M. rubra. In the present study, a total of 152 MrUGT genes clustered into 13 groups were identified in M. rubra genome. Among them, 139 MrUGT genes were marked on eight chromosomes and 13 members located on unmapped scaffolds. Gene duplication analysis indicated that expansion of MrUGT gene family was mainly forced by tandem and proximal duplication events. Gene expression patterns in different tissues and under UV-B treatment were analyzed by transcriptome. Cyanidin 3-O-glucoside (C3Glc) and quercetin 3-O-glucoside (Q3Glc) were two main flavonoid glucosides accumulated in M. rubra. UV-B treatment significantly induced C3Glc and Q3Glc accumulation in fruit. Based on comprehensively analysis of transcriptomic data and phylogenetic homology together with flavonoid accumulation patterns, MrUFGT (MrUGT78A26) and MrUGT72B67 were identified as UDP-glucosyltransferases. MrUFGT was mainly involved in C3Glc and Q3Glc accumulation in fruit, while MrUGT72B67 was mainly involved in Q3Glc accumulation in leaves and flowers. Gln375 and Gln391 were identified as important amino acids for glucosyl transfer activity of MrUFGT and MrUGT72B67 by site-directed mutagenesis, respectively. Transient expression in Nicotiana benthamiana tested the function of MrUFGT and MrUGT72B67 as glucosyltransferases. The present study provided valuable source for identification of functional UGTs involved in secondary metabolites biosynthesis in M. rubra.